ON DOUBLE – WORKING OF THE VERBAL DIATHESIS IN THE JUDGEMENTS. THE NECESSITY IN ESTABLISHING A JUDICATIVE DIATHESIS INTO THE VERB FROM A PHENOMENOLOGICAL POINT OF VIEW - Maria-Roxana BISCHIN (Studia Universitatis Babeș-Bolyai. Philosophia)
Starting with the statement that the Being is what-it-is, we have a new dilemma when we want to express something through a philosophical sentence. We will try to find out and to show how the structure of the verb, correlated with the judgement dresses up a double form: a passive one, and a reflexive one. We think the direction of transformation starts with the passive form and change into a reflexive one. This double loop of the verb, and the recent studies in judicative phenomenology, makes us to establish two new diathesis on the mental-structures of the verb: the judicative-diathesis and the pre-judicative-diathesis. Finally, in the construction of the verbs being and is still persists the double fulfillment of the passive, and reflexive, to whom we can add the active form, because in ontical plane, the verb is let to activate something - the Being. The manner on how Being is activated in judgement, is double: a pre-judicative way, and a judicative way.